Comparison of CECT and CT perfusion in differentiating benign from malignant neck nodes in oral cavity cancers. (2021) - Suryavanshi, Shubham; Kumar, Jyoti; Manchanda, Alpana; Singh, Ishwar; Khurana, Nita
Abstract: Aim: The objective of the study was to assess the performance of CT Perfusion in comparison to CECT for preoperative detection of metastases to lymph nodes in squamous cell cancers of oral cavity. Methods: Twenty-five patients with squamous cell cancers of oral cavity underwent CECT and CTP. Two radiologists evaluated CECT and CTP parameters independently. Surgery and post-operative histopathology was performed in all patients. Results: Level wise analysis of the largest node was done. 102 lymph nodes on CECT and 82 lymph nodes on CTP were correlated with post-operative histopathological findings. CECT had a sensitivity, specificity and accuracy of 75 %, 98.6 % and 91.2 %(p-value <0.001) respectively in differentiating benign from metastatic nodes. Mean transit time[MTT] was significantly the most accurate CTP parameter and carried a sensitivity, specificity, accuracy and AUC of 90.5 %, 93.4 %, 92.7 % and 0.96 (p < 0.001). The sensitivity of MTT was higher than the sensitivity of overall CECT. Conclusions: CTP is a promising tool for detection of metastatic cervical nodes in squamous cell cancers of the oral cavity.